Characterisation and optimisation of wrinkling during the forming of tufted three-dimensional composite preforms. (December 2019) - Shen, Hao; Wang, Peng; Legrand, Xavier; Liu, Lingshan
Abstract: The present paper aims to quantify and optimise the textile reinforcements forming with a complex structure, in particular, the through-thickness reinforcements by tufting. To optimize the forming process, different tufting locations and patterns are used and compared to each other. To quantify and evaluate the forming process, in particular, the wrinkling phenomenon, a Structure from Motion (SFM) based image analysis methodology is proposed. The modelling data for three-dimensional reconstruction are extracted from a stack of photographs taken around the samples. Wrinkles are identified from the deviation of the wrinkled shape from a reference shape. Different indicators are used and discussed to obtain a general view of wrinkling severity. Wrinkle pattern is critically dependent on tufting distribution, which should correspond to the punch shape to minimize wrinkles in some specific areas. Otherwise, inappropriate tufting will give rise to wrinkling severity to some extent.